(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
This article examines the evolution of enterprise data engineering through the integrationof customer and revenue data platforms. As organizations face challenges from fragmented systems and inconsistent definitions, innovative architectural approaches have emerged to create unified data ecosystems. The article explores the transformative role of master data management and identity resolution in establishing consistent entity definitions across domains. It investigates modular ELT frameworks that incorporate continuous quality validation, governance-as-code implementations that automate policy enforcement, and event-driven architectures that enable real-time synchronization between customer behavior and financial systems. The article further addresses how intelligent automation and predictive enrichment enhance data completeness while reducing manual intervention. Governance frameworks receive particular attention, including comprehensive data catalogs with lineage visualization, layered protection mechanisms for sensitive information, automated financial reconciliation models, and consent management systems that ensure regulatory compliance. The article concludes by examining sustainability considerations in enterprise data architectures, including optimization techniques that balance performance requirements with environmentalimpact.